Mobile ad hoc network testbed using mobile robot technology - Muchtar, Farkhana; Abdullah, Abdul Hanan; Abd Wahab, Mohd Helmy; Ambar, Radzi; Hanafi, Hafizul Fahri; Ahmmad, Siti Nor Zawani (IOP Publishing, 2018)
MANET (Mobile Ad Hoc Network) researchers have shown increased interest in using mobile robot technology for their testbed platforms. Thus, the main motivation of this paper is to review various robot-based MANET testbeds that have been developed in previously reported research. Additionally, suggestions to heighten mobility mechanisms by using mobile robots to be more practical, easy and inexpensive are also included in this paper, as we unveils ToMRobot, a low-cost MANET robot created from an ordinary remote control car that is capable of performing a real system MANET testbed with the addition of only a few low-cost electronic components. Despite greatly reduced costs, the ToMRobot does not sacrifice any of the necessary MANET basic structures and will still be easily customizable and upgradeable through the use of open hardware technology like Cubieboard2 and Arduino, as its robot controller. This paper will also include guidelines to enable technically limited MANET researchers to design and develop the ToMRobot. It is hoped that this paper achieves its two pronged objectives namely (i) to facilitate other MANET researchers by providing them with a source of reference that eases their decision making for selecting the best and most suitable MANET mobile robots for real mobility in their MANET testbeds (ii) to provide MANET researchers with a prospect of building their own MANET robots that can be applied in their own MANET testbed in the future.